1994
DOI: 10.1002/ijc.2910580611
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of the adenomatous polyposis coli gene in human oral squamous‐cell carcinoma

Abstract: Recent studies have suggested that abnormalities in the adenomatous polyposis coli gene (APC gene) are associated with the development not only of familial adenomatous polyposis coli (FAP) but also of cancers in digestive organs. In order to elucidate whether abnormalities of the APC gene could contribute to the development of oral squamous-cell carcinoma (SCC), genomic DNAs from tumors and normal tissues of 24 unrelated Japanese patients were examined by using PCR-SSCP (polymerase chain reaction single-strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 17 publications
2
45
0
Order By: Relevance
“…Even though there is frequent LOH on 13q (Yoo et al, 1994) there does not appear to be inactivation of the retinoblastoma gene, and it has been argued by these authors that there may be another tumour-suppressor locus at 13ql4. Also, the APC/ MCC locus on 5q, which has been demonstrated to be involved in colorectal carcinomas (Kinzler et al, 1991) and has previously been shown to have a high LOH in SCCHN (Ah-See et al, 1994), may not in fact be the target locus, as mutations in the APC gene have rarely been found in oral cancers (Uzawa et al, 1994).…”
Section: D6cusonmentioning
confidence: 99%
“…Even though there is frequent LOH on 13q (Yoo et al, 1994) there does not appear to be inactivation of the retinoblastoma gene, and it has been argued by these authors that there may be another tumour-suppressor locus at 13ql4. Also, the APC/ MCC locus on 5q, which has been demonstrated to be involved in colorectal carcinomas (Kinzler et al, 1991) and has previously been shown to have a high LOH in SCCHN (Ah-See et al, 1994), may not in fact be the target locus, as mutations in the APC gene have rarely been found in oral cancers (Uzawa et al, 1994).…”
Section: D6cusonmentioning
confidence: 99%
“…All patients had OSCC that was histologically confirmed, and tumour samples were checked to ensure the presence of tumour tissue in more than 80% of specimens. Genomic DNA was extracted as described previously (Uzawa et al, 1994); total RNA was prepared using Trizol Reagent (Invitrogen Corp., Carlsbad, CA, USA), according to the manufacturer's protocol.…”
Section: Tissue Samples and Nucleic Acid Isolationmentioning
confidence: 99%
“…with the possible exception of Ki-ras mutations in pancreatic cancer. the earliest genetic alteration in these malignancies has not yet been discovered (Honi et al 1992a: b;McKie et al 1993;Ogasawara et al 1994: Seymour et al 1994: Uzawa et al 1994; Yashima et al 1994: Hahn et al 1995.…”
mentioning
confidence: 99%